(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article analyzes the impact of inflation on Uzbekistan’s market economy from a theoretical perspective. It examines the historical dynamics of inflation, its effects on investments, employment, and purchasing power. Based on data from international organizations (IMF, World Bank, Asian Development Bank) and Uzbekistan’s legal frameworks, forecasts for 2025–2030 are provided. The article uses tables and charts for data visualization. It concludes that reducing inflation to 5% will contribute to the sustainable development of the market economy.